In quest of an improved algorithm for transforming plane triangulations by simultaneous flips - Prapty, Annesha Chowdhury; Pranty, Namira Mustafiz; Ahmed, Tasnova; Mehnaz, Tasnuba (Brac University, 2023)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science, 2022.